Analysis of structure of lumbar spine dorsopathy morbidity in able-bodied age patients - Manin M.V.; Abramov V.V.; Nekhanevich O.B.; Khaitov P.A.; Kaptelov N.I.; Sysenko I.V. (Medičnì Perspektivi)
The analysis of structure of lumbar spine dorsopathy morbidity among able-bodied population of the Dnepropetrovsk area for substantiation of differentiated approach to the choice of exercise therapy methods was a research objective. The structure of dorsopathy morbidity in 371 patients in 2009-2013 period is analysed in the work. The paper presents analysis of the most frequent morphological changes in the structures of the spine, their localization and clinical course. Link of clinical manifestations of dorsopathy with structural changes of the backbone, the disease experience is revealed, efficiency of rehabilitation by means of physiotherapy exercises depending on qualitative and quantitative signs of disease is defined. Results of the research specify that more than 40% of patients were on repeated treatment, clinical manifestation in 62% of patients was observed at the most able-bodied age (from 30 to 50 years), according to the disease experience number of aggravations per a year increased, in 57,5% of cases administration of medical physical culture was limited due to development of an accompanying pathology, in 40% of cases against positive dynamics of painful syndrome insufficient changes in volume of movements of the spine segments throughout treatment were marked. It testifies to necessity of working out algorithm of differentiated approach to the choice of means medical physical culture in treatment of lumbar spine dorsopathy.